REACTIONS AND RESPONSES OF THE CHRISTIAN DEMOCRATS PARTY AGAINST THE MILITARY COUP OF 1973: ¿COLLABORATION OR OPPOSITION? - Rubio Apiolaza, Pablo; Torres Dujisin, Isabel (Revista de Historia Social y de las Mentalidades, 2015)
This article presents an analysis of the political  strategy of the Christian Democratic Party  (PDC) during the first year of the Chilean  military dictatorship. It emphasizes its policy  of alliances and internal relations, selecting  some key junctures in its relationship with the  Popular Unity and its reaction to the Military  Coup and the first year of the dictatorship.  Through a review of its internal documentation,  the article seeks to demonstrate the dominance  of conservative positions DC, even though the  party positions are not unique, which explains  an intense internal debate at the beginning of the  dictatorship.
Keywords: Political parties; Dictatorship military; Political alliances